Investigating leadership ethnographically: Opportunities and potentialities. (June 2018) - Sutherland, Neil
Whilst recent years have seen increasingly ethnographic-focussed writings in Organisation Studies, similar developments have not been mirrored within Leadership Studies, where the field is still dominated by positivistic approaches. Various theorists have noted problems with this, often pointing toward ethnography as a way of investigating leadership from new angles. However, to date it remains underrepresented. Potentially, this could be due to the fact that leadership is an ill-defined concept, and this paper suggests developing a clearer understanding of the phenomenon – building on the work of Smircich and Morgan and Fairhurst. That is, understanding leadership as constituted by meaning-making and reality definition, which is performed through discourse (or: intersubjective talk, communication, language and interaction) as well as being influenced by Discourse (or: extrasubjective frames of reference). This paper suggests that ethnographic methodologies are apt for studying both, and may be able to shed new light on leadership practice.